THE INFLUENCE OF THE CONSTITUTIONAL JURISDICTIONS ON THE BASIC LAWS - VALENTINA BARBATEANU (Challenges of the Knowledge Society)
This paper intends to reveal the role played by the constitutional courts or other bodies entitled to perform the constitutional review of normative acts in enhancing the significance of the National Basic Laws and in developing their content. The research will try to show that the case-law created by the constitutional jurisdictions can shape the perception of the society on the Basic Law, offering a different perspective over its meaning. This is the effect of the interpretation of the Basic Law provisions, which is an inherent part of the constitutional jurisdictions’ activity.